Originally Posted by
angypangy I thought this would be relatively straightforward but I can't seem to solve myself.
x = (5 + 2y)/3
substitute into x^2 + y^2 = 2
((5+2y)/3)^2 + y^2 = 2
25/9 + 20/9y + 4/9y^2 + y^2 = 2
13/9y^2 + 20/9y + 7/9 = 0
x 9: 13y^2 + 20y + 7 = 0
using -b+-rt b^2 - 4ac
----------------
2a
a=13, b=20, c=7
it's fine to here
y= -13/20 or y = -7/20
substituting into 3x-2y=5
when y=-13/20, x = 37/50
when y = -7/20, x = 43/30
But this is incorrect because putting these x and y values into circle equation don't produce 2. Can anyone see where I have gone wrong?